MindCare: Development of Mobile Application on Mental Health Monitoring for Pusat Kesihatan Universiti UTHM - MUHAMMAD ASYRAF BIN AHMAD; MOHD ZANES BIN SAHID (Applied Information Technology And Computer Science, 2025)
Mental health is essential, but many avoid addressing it due to stigma, low awareness, and limited support access. The UTHM Health Centre relies on time-consuming, traditional in-person processes and lacks an efficient student mental health tracking method, while existing apps often lack personalized and holistic features. The project addresses the problem of inefficient mental health monitoring, which often causes delays in intervention, undetected emotional distress, and a decline in student well-being. This project uses Flutter to develop a cross-platform mobile app addressing these challenges and the app includes mood tracking, journaling, personalized self-care suggestions, and mental health resources to help students monitor and enhance their well-being. The application has been designed for the UTHM Health Centre to replace manual mental health tracking with a digital solution that improves monitoring and support. Therefore, it offers insights into student well-being, enabling better resource allocation, early interventions, and proactive mental health practices.